THE IMPLEMENTATION OF NATIONAL DEFENDING VALUES IN CIVIC LEARNING AT STAB MAITREYAWIRA PEKANBARU: ACTUALIZATION IN THE COVID-19 PANDEMIC - Jelita, Rida (Jurnal Pencerahan, 2022)
This study aimed to determine the increase in the cultivation of state defense values ​​during the Covid-19 Pandemic after the application of practical and discussion methods in the Civic Education course at the Buddhist College (STAB) Maitreyawira, Pekanbaru, Riau This study used Classroom Action Research design with 2 cycles and 4 main activities in each cycle, namely planning, acting, observing, and reflecting. The researcher took 32 students (10 male and 22 female), first semester students, the academic year 2021/2022 as the subjects of the study. The results showed that the students’ scores got improved by 62,5% in cycle I (20 students) and 87,5% in cycle 2 (28 students). Based on this, it can be concluded that the application of practice and discussion methods can increase the inculcation of state defense values ​​for STAB Maitreyawira students during the Covid-19 pandemic in citizenship education courses.